PENGARUH MOTIVASI TERHADAP PENGAJARAN INDIVIDU - Fauziah Nasution; Nurul Husna; Sabilla Ayu Andini (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
Motivation and teaching are two concepts that are interrelated and have an important role in the world of education. Motivation is a key factor influencing individual behavior and achievement, while teaching is a process that involves the teacher imparting knowledge and skills to students. In the context of education, motivation is a vital element that supports student learning success. Motivation is an internal or external drive that drives individuals to achieve certain goals or perform certain actions. It involves psychological, emotional, and social factors that influence a person's behavior. In the educational context, motivation plays an important role in motivating students to learn, participate actively in the learning process, and achieve the desired results. Meanwhile, teaching is a process that involves the teacher in conveying learning material to students. The aim of teaching is to inspire and motivate students in learning, help them understand the concepts being taught, develop skills and competencies, and encourage creativity and critical thinking.